Small random perturbations in second-order oscillatory systems - Borisenko О. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The limit behavior of the solutions of a nonlinear differential equation that describes an oscillatory system with small random perturbations of the type of multidimensional “white” and “shot” noises is studied.